EFFECTIVENESS OF INTERACTIVE METHODS IN TEACHING THE COMPOSITION OF A LITERARY WORK (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article provides a comprehensive examination of methodological approaches to teaching high school students the composition of literary works. Composition is described as one of the key concepts that organize the internal structure of a literary work, and effective methods for teaching its plot elements, character development dynamics, character conflicts, and the work’s spatial-temporal structure are analyzed. Through practical lesson examples and specific methodological tasks, the author demonstrates the impact of compositional analysis on deepening students’ literary-theoretical understanding, fostering their creative thinking, and enabling comprehensive text interpretation. Additionally, the article presents methodological tools, group and individual work formats, as well as interactive approaches to effectively teach compositional structure. These approaches ensure students’ systematic perception of literary works and aim to develop their analytical and critical thinking skills.